2015
DOI: 10.1182/blood-2015-05-642223
|View full text |Cite
|
Sign up to set email alerts
|

Oral iron supplements increase hepcidin and decrease iron absorption from daily or twice-daily doses in iron-depleted young women

Abstract: Physicians and Surgeons, New York, NY Key Points• Iron supplements at doses of 60 mg Fe as FeSO 4 or higher increase hepcidin for up to 24 hours and are associated with lower iron absorption on the following day.• The soluble transferrin receptor/ferritin ratio and hepcidin are equivalent predictors of iron absorption from supplements.Iron supplements acutely increase hepcidin, but the duration and magnitude of the increase, its dose dependence, and its effects on subsequent iron absorption have not been chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
336
3
22

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 425 publications
(371 citation statements)
references
References 33 publications
10
336
3
22
Order By: Relevance
“…However, oral iron acutely increases hepcidin and recent data suggest that twice and thrice daily supplementation may have little added benefit over oncedaily dosing. 41 Two weeks after starting oral iron, a Hb increase of 1 g or more suggests adequate absorption. 42 Replacement should be continued until iron stores are replenished (generally 2-3 months), and 6 weeks postpartum.…”
Section: Hepcidinmentioning
confidence: 99%
“…However, oral iron acutely increases hepcidin and recent data suggest that twice and thrice daily supplementation may have little added benefit over oncedaily dosing. 41 Two weeks after starting oral iron, a Hb increase of 1 g or more suggests adequate absorption. 42 Replacement should be continued until iron stores are replenished (generally 2-3 months), and 6 weeks postpartum.…”
Section: Hepcidinmentioning
confidence: 99%
“…An already established major advance in oral iron therapy deriving from hepcidin discovery is related to the administration schedule. An elegant pilot-study by Moretti and colleagues on non-anemic ID premenopausal women suggested that giving oral iron on an alternate day schedule might be as effective as the classical daily schedule based on divided doses [81]. The classical schedule was associated to a rapid response in hepcidin production that limited the absorption of a second dose given too early.…”
Section: Oral Iron Therapy In the Hepcidin Eramentioning
confidence: 99%
“…17,18 Alternatively, and in the absence of point-of-care ferritin platforms, development of ID in donors may be prevented by (1) prolongation of donation intervals to 180 days in all donors as suggested by both the current and the REDS-III study 16 and/or (2) (low) dose iron supplementation. 24 …”
mentioning
confidence: 99%